The Influence of Total Physical Response Method using Flash Card toward English Vocabulary Mastery for Early Childhood (Journal of Primary Education, 2020)
This research aim is to investigate the influence of Total Physical Response method in the use of Flash Card to enhance childrenâ€™s English vocabulary of group B in RA Islamic Tunas Bangsa 4 Ngaliyan. Method of this research was used experiment approach of non equivalent pre test-post test control group design. Sampling technique of this research was used random sampling technique. In this research, the sample was 36 children that were devided into 2 groups. 18 children were in the experimental group and 18 chidren were in the control group. Collecting data was used test, observation, questionarie, interview and documentation. Furthermore, data analysis was used t-test. Based on the research, Total Physical Response method using flash card has influence on the increasing of the children English vocabulary. It was shown of the t-test value which is tcount 5.407 â‰¥ 2.101 with the significant level Î± = 0.05. The success was caused by the stimulation of introducing English vocabularies through the media of Flash Card. It gave good outcome for children which is they able to pronounce the words, scrutinized the words, familiar with the words and understand the meaning of the words. Therefore, it can be said that this research had been proved that there was significant result of Total Physical Response method using Flash Card towars children English vocabulary mastery in RA Islamic Tunas Bangsa 4 Ngaliyan.